Factors associated with ruptured ectopic pregnancy: a systematic review - Saloumeh Peivandi; Ali Habibi (Mashhad University of Medical Sciences, 2023)
Introduction: ectopic pregnancy (EP) refers to implanting a fertilized egg outside the uterine cavity. A ruptured ectopic pregnancy is the main cause of maternal mortality in the first trimester of pregnancy. The present study was performed with aim to systematically review the factors related to ruptured ectopic pregnancy. Methods: This systematic review study was conducted based on the PRISMA checklist. An extensive search was performed in the internal and external databases, including PubMed, Magiran, Web of Science, Scopus, SID, and Google Scholar search engine using the keywords extracted from Mesh, including Extrauterine Pregnancy, Ectopic Pregnancies, Abdominal Pregnancy, Heterotopic Pregnancy, Ovarian Pregnancy, Tubal Pregnancy, Interstitial Pregnancy, Perforation, Rupture, Factors, Related Factors and also their Persian equivalent with all possible and main combinations from the beginning to March 12, 2023. Results: A total of 10 articles out of 624 studies, including 3475 pregnant women were included in the study. Of these, about 1351 people (38%) had a ruptured ectopic pregnancy with mean age of 30.1±5.62 years. Factors such as β-hCG hormone level (5 cases), gestational age weeks (2 cases), and history of ectopic pregnancy (2 cases) were among the factors related to ectopic pregnancy. Conclusion: The present study showed that factors such as β-hCG level, age, history of EP, gestational age, history of pelvic infectious diseases (PID) and use of contraceptives are related to ruptured ectopic pregnancy (REP).